Characterising the chemistry of micropores in a sodic soil with strong texture-contrast using synchrotron X-ray techniques and LA-ICP-MS - Jassogne, Laurence; Hettiarachchi, Ganga M.; McNeill, Ann; Chittleborough, David (My University, 2013)
Soils with strong texture-contrast between A and B horizons dominate the agricultural zones of the west and south of Australia. The B horizon is often sodic and of much finer texture than the A (or E) horizon above, and can have a bulk density as high as 2 g cm–3. When dry, these B horizons may severely impede the root growth of annual cereal crops. The objective of this study was to characterise the mineralogy and chemistry of fine pores at the interface of an E and a sodic B horizon of an Alfisol (Sodosol). Micro-X-ray fluorescence spectroscopy (μ-XRF) was used to locate the distribution of calcium (Ca), manganese (Mn), iron (Fe), zinc (Zn), and copper (Cu), and μ-X-ray absorption near edge structure (μ-XANES) spectroscopy or μ-X-ray absorption fine structure (μ-XAFS) spectroscopy to investigate speciation of Fe, Mn, Zn, and Cu around a pore. Both natural aggregates and thin sections were employed but measurements from thin sections were more useful because of the smaller thickness of the sample. The distribution maps showed that Ca was present in the pores but the other elements were not. Copper, Mn, and Zn were concentrated around the micropore. Manganese was always well correlated with Fe. Manganese was found in reduced form, i.e. Mn(II), and associated with phosphates, whereas Fe was in oxidised form and mostly associated with oxides. Zinc was mostly associated with carbonates (CO3), sulfates (SO4), and silicates (SiO4). The results were then compared with measurements by laser ablation inductively coupled plasma-mass spectrometry (LA-ICP-MS). Only some of the observations made by μ-XRF were confirmed by LA-ICP-MS, most probably because of the superior detection limits of synchrotron-based μ-XRF.
Citation: Jassogne Laurence, Hettiarachchi Ganga, McNeill Ann, Chittleborough David (2012) Characterising the chemistry of micropores in a sodic soil with strong texture-contrast using synchrotron X-ray techniques and LA-ICP-MS. Soil Research 50, 424-435.
Keywords: Micropores; Soil; Soil texture; Sodic soil